Modulation of Cytokine Production by Drugs with Antiepileptic or Mood Stabilizer Properties in Anti-CD3- and Anti-CD40-Stimulated Blood In Vitro. (16th March 2014) - Himmerich, Hubertus; Bartsch, Stefanie; Hamer, Hajo; Mergl, Roland; Schönherr, Jeremias; Petersein, Charlotte; Munzer, Alexander; Kirkby, Kenneth Clifford; Bauer, Katrin; Sack, Ulrich
Abstract : Increased cytokine production possibly due to oxidative stress has repeatedly been shown to play a pivotal role in the pathophysiology of epilepsy and bipolar disorder. Recent in vitro and animal studies of valproic acid (VPA) report antioxidative and anti-inflammatory properties, and suppression of interleukin (IL)-6 and tumor necrosis factor (TNF)- α . We tested the effect of drugs with antiepileptic or mood stabilizer properties, namely, primidone (PRM), carbamazepine (CBZ), levetiracetam (LEV), lamotrigine (LTG), VPA, oxcarbazepine (OXC), topiramate (TPM), phenobarbital (PB), and lithium on the production of the following cytokines in vitro : interleukin (IL)-1 β, IL-2, IL-4, IL-6, IL-17, IL-22, and TNF- α . We performed a whole blood assay with stimulated blood of 14 healthy female subjects. Anti-human CD3 monoclonal antibody OKT3, combined with 5C3 antibody against CD40, was used as stimulant. We found a significant reduction of IL-1 and IL-2 levels with all tested drugs other than lithium in the CD3/5C3-stimulated blood; VPA led to a decrease in IL-1 β, IL-2, IL-4, IL-6, IL-17, and TNF- α production, which substantiates and adds knowledge to current hypotheses on VPA's anti-inflammatory properties.